2022
DOI: 10.1371/journal.pone.0262149
|View full text |Cite
|
Sign up to set email alerts
|

FluoRNT: A robust, efficient assay for the detection of neutralising antibodies against yellow fever virus 17D

Abstract: There is an urgent need for better diagnostic and analytical methods for vaccine research and infection control in virology. This has been highlighted by recently emerging viral epidemics and pandemics (Zika, SARS-CoV-2), and recurring viral outbreaks like the yellow fever outbreaks in Angola and the Democratic Republic of Congo (2016) and in Brazil (2016–2018). Current assays to determine neutralising activity against viral infections in sera are costly in time and equipment and suffer from high variability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Specifically, a study on PRNT for dengue virus that served as a model to our study, showed similar performances for the 4 dengue serotypes 18 . Beyond the PRNT methods using live virus, other types of YF PRNT have been developed and evaluated to measure neutralizing antibodies such as Focus Reduction Neutralization Test (FRNT) and the Fluorescence Reduction Neutralization Test (FluoRNT) which showed respective precision performances of 91.7% and 94.9% in 28 days postvaccinated subjects 27 . Taking together, these data showed that the PRNT we developed here for YFV is consistent and reliable enough for use in diagnostic and evaluation of vaccine efficacy 28 …”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Specifically, a study on PRNT for dengue virus that served as a model to our study, showed similar performances for the 4 dengue serotypes 18 . Beyond the PRNT methods using live virus, other types of YF PRNT have been developed and evaluated to measure neutralizing antibodies such as Focus Reduction Neutralization Test (FRNT) and the Fluorescence Reduction Neutralization Test (FluoRNT) which showed respective precision performances of 91.7% and 94.9% in 28 days postvaccinated subjects 27 . Taking together, these data showed that the PRNT we developed here for YFV is consistent and reliable enough for use in diagnostic and evaluation of vaccine efficacy 28 …”
Section: Discussionsupporting
confidence: 54%
“…18 Beyond the PRNT methods using live virus, T A B L E 5 Accuracy/dilutability of PRNT90 yellow fever virus. 27 Taking together, these data showed that the PRNT we developed here for YFV is consistent and reliable enough for use in diagnostic and evaluation of vaccine efficacy. 28 In addition to these assay performance evaluations, our PRNT presents other advantages including a shorter turn-around time, 4-5 days, compared with others YF PRNT protocols that take 6-7 days.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…There are methods in place to characterize functional Nt-Ab responses to the Poliovirus and Yellow fever virus, for which well-tested and proven vaccines are available [2,11,19,49,67]. Different types of NTs based on either viral plaque or focus staining procedures have been developed for the VPDs, i.e., Measles virus (MeV), Mumps virus (MuV), Rubella (RuV) and Varicella Zoster virus [7,10,13,16,21,22,[38][39][40][41][42][43][44][45]55,56,65,68].…”
Section: Measurement Of Neutralizing Antibodies To Public Health-impo...mentioning
confidence: 99%